Improved germination efficiency of Salicornia ramosissima seeds inoculated with Bacillus aryabhattai SP1016‐20 - Figueira, Carolina (2020)
Saline agriculture and the crop cultivation of halophytes represent an alternative for the reclamation of salinized soils and for the management of irrigation water. Halotolerant plant growth promoting bacteria with biocontrol effect, as an alternative to commercial fungicides, may contribute to improve crop productivity while mitigating saline stress effects. The objective of this work was to isolate autochthonous rhizobacteria with biocontrol features, to be used as germination enhancers and plant-growth promoting agents in the crop cultivation of Salicornia ramosissima. A set of isolates obtained from the rhizosphere of S. ramosissima was characterised in terms of Gram, motility, salt tolerance and biocontrol traits (hydrogen cyanide production, antifungal activity and production of extracellular lipases and proteases). One Gram-positive motile isolate that tested positive for all biocontrol traits was identified by 16S rRNA gene sequencing as Bacillus aryabhattai. The inoculation of S. ramosissima seeds with B. aryabhattai SP1016-20 reduced the negative effect of salinity on the germination efficiency. At the highest tested salinity (30 g/L NaCl) the final germination efficiency of inoculated seeds doubled in relation to noninoculated controls. Although the mechanisms involved in the biocontrol effect were not defined in the current work, the results highlight the potential of Bacillus aryabhattai SP1016-20 as a plant-growth promoting agent for the crop cultivation of Salicornia and contribute to the strengthening of the scientific basis of biosaline agriculture and plant growth promoting rhizobacteria-assisted crop cultivation of halophytes in saline soils and estuarine sediments.